2017
DOI: 10.3892/etm.2017.4924
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of PTPN1 promoter methylation is a significant risk factor of type 2 diabetes in the Chinese population

Abstract: The present study aimed to investigate the contribution of DNA methylation of the protein tyrosine phosphatase, non-receptor type 1 (PTPN1) gene to the susceptibility to type 2 diabetes (T2D). Peripheral blood mononuclear cells (PBMCs) were collected from 97 patients with T2D and 97 age- and gender-matched controls. DNA methylation of the PTPN1 gene promoter was evaluated by bisulfite pyrosequencing. Independent sample t-tests were used to compare the differences in the PTPN1 promoter and other phenotypes betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…More recently, Huang et al investigated the methylation status of another key regulator of the insulin signaling pathway, PTPN1 , in relation to T2D susceptibility (50). PTPN1 encodes the protein-tyrosine phosphatase 1B protein, which attenuates the insulin signaling pathway by decreasing the phosphorylation of the insulin receptor and/or insulin receptor substrate 1 (68).…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…More recently, Huang et al investigated the methylation status of another key regulator of the insulin signaling pathway, PTPN1 , in relation to T2D susceptibility (50). PTPN1 encodes the protein-tyrosine phosphatase 1B protein, which attenuates the insulin signaling pathway by decreasing the phosphorylation of the insulin receptor and/or insulin receptor substrate 1 (68).…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…In three candidate gene-studies PTPN1 [32], PLA2G7 [26] and BCL11A [27] DNAm was positively associated with serum lipids in women, but not in men. Another study reported that methylation at ABCG1 was negatively associated with triglycerides in women only [28], whereas methylation at LIPC was negatively associated with triglycerides only in men [27].…”
Section: Blood Lipidsmentioning
confidence: 90%
“…Global DNA methylation is a frequent used marker for epigenetic screening since it captures the DNA methylation also at unknown genetic locations while the results of average DNA methylation correlate with the methylation of some trait-relevant genes [23,24]. Ten articles [14,[25][26][27][28][29][30][31][32][33] investigated sex-specific associations between DNAm and blood lipid concentrations applying global n = 2, epi-genome wide n = 1 and candidate gene n = 7 approaches. In total 2,443 non-overlapping participants 1,174 women and 1,269 men from USA, Canada, Finland, UK and China were included in these studies.…”
Section: Blood Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into the association between T2DM susceptibility and the DNA methylation status of the PTPN1 gene found a significant correlation between the risk for T2DM and the hypermethylation of the eight CpGs in the PTPN1 promoter. A further breakdown analysis by gender showed that this correlation was female specific, as no significant differences were observed between T2DM males and control males in terms of PTPN1 methylation [ 33 ].…”
Section: Single or Multiple Gene Studiesmentioning
confidence: 99%